Metastasis to the breast from thyroid cancer: A rare case (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2023)
There are very few cases described in the literature on thyroid metastasis to other organs, but it is even rarer to find metastasis of thyroid cancer to the breast, 0.5% to 1%. Breast metastases can simulate primary tumors both clinically and radiologically, requiring an accurate histological diagnosis for the correct therapeutic approach and given the prognostic implications they entail.The neoplasms that do so most frequently are in descending order of frequency: lymphomas (17%), melanomas (15%), rhabdomyosarcomas (12%), and lung carcinomas (8%), among others. The case is of a 79-year-old woman, with a history of radical thyroidectomy for 25 years, who attended due to an increase in volume, tumor mass, in the left cervical region (locoregional) and tumor mass in the lower quadrant left mammary region. internal, not painful without inflammatory manifestations.
Keywords: thyroid cancer; breast metastasis